A Local Wisdom in East Flores and the Shift: The Transition of the Lamaholot Religion to the Catholic Religion - Kebingin, Benedikta Yosefina; Martasudjita, Emanuel (Advances in Social Sciences Research Journal, 2022)
This study aims, firstly, to determine the factors that led to the conversion of the Lamaholot religion to the Larantuka Catholic religion. Second, to find out the social impact upon religious conversion of Lamaholot to Catholicism on the daily life of the people in Larantuka. And how this will gave us the basic understanding upon the history of the transition and how Catholic religion still thriving till nowadays. This study uses a qualitative method with an ethnographic approach. The research locations are spread across three sub-districts, namely Larantuka, Lewolema, and Ilemandiri. Sources of data obtained through document analysis, interviews focused on key informants, direct involvement, observation and introspection. The research results were analyzed using domain, taxonomy, and componential techniques. The theology paradigm used on this writing is the Theology of the Incarnation. How God humanizes and enters the local culture, illuminates it with divine light so that the adherents of the culture can see into the depths of themselves the truth that comes from that light.